Analisis Keterkaitan Persepsi Gizi dan Citra Tubuh (Body Image) pada Atlet Beladiri di Pusat Pendidikan dan Latihan Olahraga Pelajar Jawa Barat - Latiefah, Halwiyana Ziyanka; Sulastri, Afianti; Sutrisno, Imam Tri; Putri, Suci Tuty; Darmawati, Irma; Salasa, Sehabudin (Institut Teknologi Bandung, 2024)
Body weight is a crucial aspect in martial arts sports, as it is directly related to determining the competition class that an athlete will participate in. To achieve their ideal target weight required for their respective classes, each athlete has their own perception of the body weight status they desire. This perception is often closely linked to their body image or view of their current physical form. This research was conducted with the aim of comprehensively describing nutritional perceptions, body image profiles, and the relationship between nutritional perceptions and body image among martial arts athletes at the West Java Student Sports Education and Training Center (PPLP). This research involved 45 martial arts athletes from the West Java PPLP institution, comprising 25 males and 20 females. The research design used was a cross-sectional survey with total sampling technique. Nutritional perception and body image assessments were conducted using the Nutritional Perception Screening Questionnaire (NPSQ9) and Figure Rating Scale (FRS) instruments. The findings showed that on average, the athletes' nutritional perceptions were in the good category. However, the obtained body image profile yielded negative results, meaning that their current body shape did not match the desired body shape of the athletes. The bivariate correlation analysis revealed no significant relationship between nutritional perceptions and body image among martial arts athletes at the West Java PPLP, with a significance value of 0.164 (p>0.05). Although the body image profiles of males were negative and females positive, there was no difference in perception between them. This was because the athletes were more focused on meeting the requirements for their competition class rather than attaining their desired body image.